2018
DOI: 10.3390/nu10081008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol and Drugs of Abuse on Maternal Nutritional Profile during Pregnancy

Abstract: The consumption of alcohol and drugs of abuse among pregnant women has experienced a significant increase in the last decades. Suitable maternal nutritional status is crucial to maintain the optimal environment for fetal development but if consumption of alcohol or drugs of abuse disrupt the intake of nutrients, the potential teratogenic effects of these substances increase. Despite evidence of the importance of nutrition in addicted pregnant women, there is a lack of information on the effects of alcohol and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 79 publications
0
69
0
3
Order By: Relevance
“…Exposure to drugs and teratogens during pregnancy are associated with IUGR. Cigarette, opiate, alcohol, and cocaine use cause fetal growth restriction directly and by decreasing maternal food intake (140,141). Even prescription medications like anticonvulsants, antineoplastic agents, and antithrombotic drugs are teratogens and can result in fetal growth restriction (142,143).…”
Section: Current Understanding In Causes Of Iugrmentioning
confidence: 99%
“…Exposure to drugs and teratogens during pregnancy are associated with IUGR. Cigarette, opiate, alcohol, and cocaine use cause fetal growth restriction directly and by decreasing maternal food intake (140,141). Even prescription medications like anticonvulsants, antineoplastic agents, and antithrombotic drugs are teratogens and can result in fetal growth restriction (142,143).…”
Section: Current Understanding In Causes Of Iugrmentioning
confidence: 99%
“…Moreover, alcohol consumption can interfere with the absorption of nutrients, impairing the quality and quantity of proper nutrient and energy intake, resulting in malnutrition especially of micronutrients such as vitamins, omega-3, folic acid, zinc, choline, iron, copper, and selenium [63]. When maternal nutritional status is compromised by alcohol the supply of essential nutrients are not available for the fetus; this can result in fetal abnormalities like Intrauterine Growth Restriction, Fetal Alcohol Spectrum Disorder [64], low birth weight (21), and small for gestational age (22). This indicated the need of alcohol consumption intervention program among pregnant women to prevent these adverse pregnancy outcomes.…”
Section: Plos Onementioning
confidence: 99%
“…Fetal alcohol spectrum disorders (FASD) encompass all alcohol-related birth defects including fetal alcohol syndrome and alcohol-related neurodevelopmental disorders. Since alcohol consumption can aggravate nutrient deficiencies, it has been suggested that maternal nutritional status plays a role in the risk for FASD (3)(4)(5). In addition, rates of cigarette smoking during pregnancy are often higher among women who consume alcohol creating additional consequences to nutritional status, as well as increasing odd ratios for preterm birth, low birth weight, and growth restriction beyond either alcohol or cigarette use alone (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%